Delayed winter pruning in ‘Chardonnay’ and ‘Pinot Noir’ (Vitis vinifera L.) in Serra Gaúcha – an alternative for late frost? - Aline Mabel Rosa; Mikael Márcio Benati; Daniel Antunes Souza; Flávio Bello Fialho; Gilmar Arduino Bettio Marodin; Henrique Pessoa dos Santos (Revista Brasileira de Fruticultura, 2024)
Abstract: The use of early budding varieties in regions prone to late frosts may limit production in certain cycles. Since budburst begins in the apical buds, delaying winter pruning can be a management strategy to minimize frost risk. This study aimed to evaluate the effects of different pruning dates during the winter/spring transition in ‘Chardonnay’ and ‘Pinot Noir’ (Vitis vinifera L.) on yield components. Plants were trained using the I-trellis system, and pruned at 15-day intervals from July to October, using cordon spur pruning (two-bud spurs). Pruning conducted after the beginning of September, when apical shoots had more than three expanded leaves, significantly reduced (90%) the yield per plant. This reduction was directly associated with necrosis of primary buds in the base of canes, which stimulated sprouting of secondary or tertiary buds, which do not bear clusters. Delaying winter pruning could be an option for ‘Chardonnay’ and ‘Pinot Noir’, but apical shoot development should be limited to 2-3 expanded leaves, in order to avoid production losses.